Analisis Korosi Pada Inside Water Wall Tube PLTU Tarahan Unit 3 Lampung - Ammar Asof; Ucok Nelwan P (JURNAL POWERPLANT, 2013)
Results of chemical composition analysis and EDS (Energy Dispersive X-ray spectroscopy) on waterwall tube boiler, Unit 3 EVAL Lampung2x100 MW power plant, has mengalamikorosi showed early (initial corrosion), and observed the chlorine element content of 0.48%, which spurred the initial padapermukaan corrosion inside diameter of the tube waterwall. This indicates that there has been a difusitas chlorine on the surface of the waterwall tube diameter, which is the cause of the onset of corrosion on the waterwall tube, after the vines and get in on the inside and spread to the other side. This confirmed the results of an electron microscope photograph with magnification 1000X and 1500X. Most likely the difusitas chlorine process is caused by chlorine dissolved in the raw water boiler.